Environmental DNA reveals a mismatch between diversity facets of Amazonian fishes in response to contrasting geographical, environmental and anthropogenic effects. Issue 7 (27th November 2022) - Coutant, Opale; Jézéquel, Céline; Mokany, Karel; Cantera, Isabel; Covain, Raphaël; Valentini, Alice; Dejean, Tony; Brosse, Sébastien; Murienne, Jérôme
Abstract: Freshwater ecosystems are among the most endangered ecosystem in the world. Understanding how human activities affect these ecosystems requires disentangling and quantifying the contribution of the factors driving community assembly. While it has been largely studied in temperate freshwaters, tropical ecosystems remain challenging to study due to the high species richness and the lack of knowledge on species distribution. Here, the use of eDNA‐based fish inventories combined to a community‐level modelling approach allowed depicting of assembly rules and quantifying the relative contribution of geographic, environmental and anthropic factors to fish assembly. We then used the model predictions to map spatial biodiversity and assess the representativity of sites surveyed in French Guiana within the EU Water Framework Directive (WFD) and highlighted areas that should host unique freshwater fish assemblages. We demonstrated a mismatch between the taxonomic and functional diversity. Taxonomic assemblages between but also within basins were mainly the results of dispersal limitation resulting from basin isolation and natural river barriers. Contrastingly, functional assemblages were ruled by environmental and anthropic factors. The regional mapping of fish diversity indicated that the sites surveyed within the EU WFD had a better representativity of the regional functional diversity than taxonomic diversity. Importantly, we also showed that the assemblages expected to be the most altered by anthropic factors were the most poorly represented in terms of functional diversity in the surveyed sites. The predictions of unique functional and taxonomic assemblages could, therefore, guide the establishment of new survey sites to increase fish diversity representativity and improve this monitoring program. Abstract : By combining eDNA‐based inventories and β‐diversity models, we revealed a mismatch between the taxonomic and the functional diversity of Neotropical fishes. Taxonomic assemblages between and within basins were mainly structured by dispersal limitation while functional assemblages were ruled by environmental and anthropic factors. Mapping the regional fish diversity, we showed that the sites surveyed within the EU water framework directive had a better representativity of the regional functional diversity than taxonomic diversity and that the assemblages expected to be the most altered by anthropic factors were the less represented in terms of functional diversity in these surveyed sites.